POLITIK HUKUM PEMBATASAN TEMPAT PRAKTIK DOKTER - Ilfani Helwina Rosaria (Jurnal Magister Hukum Perspektif, 2019)
This article aims to discuss about the legal arrangements against of based on legal policy in Indonesia. With restrictions on the place of practice creates legal uncertainly. Forms of constitutional loss experienced by doctors are reduced or limited space for the medical profession. Meanwhile, on the other hand, the restrictions on the place of practice make public access to obtain and choose adequate and quality health services no longer possible to actualize properly, considering that safe, quality and affordable health services are also the right of all Indonesian people. Type of this research is normative juridical research, with the approach of related laws and regulations, the collection of legal materials is carried out by literature study, namely collecting legal materials with a systematic method. The obtained data were then collected and analized in depth, then submitted descriptive qualitatively. The results showed that the restrictions of doctor’s practice license in three places as regulated in Article 37 paragraph (2) of the Medical Practice Law is based on various considerations and wich is not contradicting with the 1945 Constitution of the Republic of Indonesia. In addition, it can provide legal protection for doctors as health provider as well and the patients as health receiver. Keywords: Legal Policy, Restrictions, Doctor’s practice